Freshwater Fishing for Kids - Howard, Melanie A. (North Mankato, Minn. : Capstone Press, 2013)
Describes freshwater fishing, including its history, gear, techniques, and safety.
The green-eyed monster -- Hook, line, and sinker -- Fishing safety -- Conservation.
Includes bibliographical references (p. 31) and index.
"RL: 3-4, IL: 3-9"--P. [4] of cover.
Accelerated Reader AR
Keywords: Fishing -- Juvenile literature; Freshwater fishes -- Juvenile literature